Facebook Addiction, Game online, Physical Health Among Indonesian Students - Hutapea, Dwight Mahaputera Marulitua; Sitopu, Robin Ferdiansyah; Silalahi, Kristina L; Halawa, Afeus; Munthe, Dewi Sartika; Siregar, Ryskina Fatimah (Universitas Prima Indonesia, 2024)
This study is essential for students to know about Facebook addiction, Game online, and physical health. The study aims to describe the level of Facebook addiction, play online, and physical health and examine their relationship. The total sample was 206 people selected using the purposive sampling method. The research design was correlational; two hundred-six participants joined this study. Each participant filled out all of the questionnaires (demographic data, the Bergen Facebook Addiction (BFAS), Game Addiction (GAS), and Physical Questionnaire (PHQ). All questionnaires were taken from the previous research and validated; the reliability test was high. Based on the Pearson correlation tests, relationships were shown between Facebook addiction, games online, and physical health. There is a significant positive correlation between Facebook addiction and physical health and games online and physical health. Facebook addiction has a positive impact on physical health. Facebook addiction will impact a student's physical health. This study findings that Facebook addiction is low level, game online moderate level, and moderate level of physical fitness. The best way to prevent students from Facebook addiction is to make them busy with school activities. Games online also have a positive impact on physical health. The longer we play the Game online, the more physical health problems we will have. Say no to Facebook addiction and games online.